The IclR-family transcriptional regulator XyrR controls flotation, motility, antibiotic production and virulence in Serratia sp. ATCC 39006 - Carlo Miguel Castro Sandoval; Carlo Miguel Castro Sandoval; George P. C. Salmond (Frontiers in Microbiology)
The opportunistic pathogen Serratia sp. ATCC 39006 (S39006) is a rod-shaped, motile, Gram-negative bacterium that produces a 𝛽-lactam antibiotic (a carbapenem) and a bioactive red-pigmented tripyrrole antibiotic, prodigiosin. It is also the only known enterobacterium that naturally produces intracellular gas vesicles (GVs), enabling cells to float in static water columns. Regulation of GVs and secondary metabolites in S39006 can be coordinated but such pleiotropy is still poorly understood. To uncover novel inputs to this complex regulatory network, we used transposon mutagenesis to identify a mutant with an insertion in an IclR-type transcriptional regulator gene. The iclR mutant showed diminished production of carbapenem, prodigiosin, GVs and cellulase. Furthermore, the mutant also showed increased swimming and swarming motilities but exhibited attenuated virulence in planta and ability to kill the nematode C. elegans. Using differential expression analysis of the intracellular proteomes of the wild type and iclR mutant, we confirmed that the mutation negatively impacted expression of the corresponding GV, carbapenem and prodigiosin gene clusters. In contrast, flagellar and chemotaxis proteins were overexpressed, consistent with the increased motility of the mutant. We also found that the proteins encoded by a putative yagEF-yjhF operon, involved in xylonate catabolism and transport, showed a 5- to 7-fold increase in expression. Finally, we show that IclR is a repressor of xylonate catabolism in S39006 and suggest that xylonate is potentially involved in controlling carbapenem and prodigiosin biosynthesis. Our results indicate that IclR is a global regulator that controls antibiotic biosynthesis, flotation through modulating GV assembly, and has pleiotropic impacts on the physiology and virulence of S39006. Based on these findings, we propose the designation of this IclR-family transcriptional regulator as XyrR (Xylonate response Regulator).